THE INFLUENCE OF EDUCATIONAL LEVEL, BUSINESS SCALE, BUSINESS EXPERIENCE AND SOCIALIZATION ON THE PREPARATION OF FINANCIAL REPORTS ACCORDING TO SAK EMKM ON COMPUTER MSMEs IN MALANG CITY - Huda, Nur; Murdiansyah, Isnan (Universitas Muhammadiyah Tangerang, 2024)
AbstractThis study was conducted to determine the effect of education level, business scale, business experience and socialization on the preparation of financial statements according to SAK EMKM on computer MSMEs in Malang City. The data used in this study are primary data by distributing questionnaires to owners of Micro, Small and Medium Enterprises (MSMEs) in Malang City. The sampling technique used the Lemeshow formula and obtained a sample of 96 MSMEs. The data analysis technique consists of validity and reliability tests, descriptive analysis, classical assumption tests, multiple liner regression analysis, simultaneous tests (F), partial tests (t), and determination coefficient tests (R^2) with the help of SPSS 23. Based on the results of the study, it shows that the level of education, business scale, business experience and socialization on the preparation of financial statements in accordance with the Financial Accounting Standards of Micro, Small and Medium Entities. However, business scale and socialization have an influence on the preparation of financial statements in accordance with SAK EMKM on Computer MSMEs in Malang City.Keywords: Effect of Education Level, Business Scale, Business Experience, Socialization, Preparation of Financial Statements in accordance with SAK EMKM in Computer MSMEs.